2001
DOI: 10.1046/j.1523-1747.2001.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Expressed in Human Keratinocytes with Long-Term In Vitro Growth Potential is Required for Cell Growth

Abstract: The herpes simplex virus large subunit of ribonucleotide reductase differs from its counterparts in eukaryotic and prokaryotic cells and in other viruses in that it contains a unique domain that codes for a distinct serine-threonine protein kinase that activates the Ras/MEK/MAPK mitogenic pathway and is required for virus growth. Previous studies suggested that ribonucleotide reductase protein kinase was co-opted from a cellular gene. Cellular genes similar to ribonucleotide reductase protein kinase were not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 73 publications
(129 reference statements)
0
34
0
Order By: Relevance
“…The percentage of apoptotic cells increased with time after H11 induction and was maximal at 7-9 days post-treatment (4 -6 days after induction of H11 expression). However, heat shockinduced H11 overexpression did not trigger apoptosis in HEK293 cells, and H11 is abundantly expressed in proliferating (basal) keratinocytes (30), suggesting that its apoptotic activity is cell type-specific.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The percentage of apoptotic cells increased with time after H11 induction and was maximal at 7-9 days post-treatment (4 -6 days after induction of H11 expression). However, heat shockinduced H11 overexpression did not trigger apoptosis in HEK293 cells, and H11 is abundantly expressed in proliferating (basal) keratinocytes (30), suggesting that its apoptotic activity is cell type-specific.…”
Section: Discussionmentioning
confidence: 93%
“…Our studies were stimulated by previous observations that H11, the eukaryotic homologue of a viral protein with cell regulatory potential, differs from canonical Hsp in that it is associated with the cell surface, has auto-and transphosphorylating PK activity, is silenced by cell differentiation (18,21,30), and does not translocate to the nucleus upon heat shock. 2 Multiple tissue arrays confirmed previous reports that constitutive H11 expression is tissue-restricted, with a hierarchy and distribution pattern similar to that of other members of the small Hsp subfamily (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that (i) expression of ICP10 PK is required for stress-induced HSV-2 reactivation from ganglionic latency (3) and (ii) ICP10 PK is homologous to a newly identified heat shock protein (4,77). Together with these findings and recent conclusions that the heat shock protein gene family is a distinct class of apoptosis regulatory proteins (28), our data indicate that expression of heat shock protein homologues is a novel mechanism for virus-induced antiapoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…While in this and other reports HSP22 was characterized as an sHSP (2,3), in some reports the newly described protein was classified as a protein kinase with similarity to the Herpes simplex protein kinase ICP10 (4 -6). HSP22 occurs preferentially in striated and smooth muscles, but also in brain (1), estrogen receptorpositive breast cancer cells (2), melanoma cells (4), and keratinocytes (5). In addition to HSP22, also abundant in muscles are other sHSPs including HSP27, myotonic dystrophy kinasebinding protein (MKBP, HSPB2), HSPB3, ␣B-crystallin (␣B-Cry, HSPB5), HSP20 (HSPB6), and cvHSP (HSPB7) (7,8).…”
mentioning
confidence: 99%